Selenium deficiency fastens intestinal barrier dysfunction and inflammation during high-fat/high-fructose-induced MASLD development in male mice - Nora Meinhardt; Anja R. Geisler; Laura Otto; Yvonne Hupfer; Betty Hebecker; Bill J. Perkowski; Markus Werner; Kristina Lossow; Marcus Ebert; Sandra Burghoff; Oliver Werz; Stefan Lorkowski; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Soil Nitrogen Supply Exerts Largest Influence on Leaf Nitrogen in Environments with the Greatest Leaf Nitrogen Demand - Alissar Cheaib; Elizabeth F. Waring; Risa McNellis; Evan A. Perkowski; Jason P. Martina; Eric W. Seabloom; Elizabeth T. Borer; Peter A. Wilfahrt; Ning Dong; Iain Colin Prentice; Ian J. Wright; Sally A. Power; et al. (Ecology Letters, 2025)
Accurately representing the relationships between nitrogen supply and photosynthesis is crucial for reliably predicting carbon–nitrogen cycle coupling in Earth System Models (ESMs). Most ESMs assume positive correlations amongst soil nitrogen supply, leaf nitrogen content, and photosynthetic capacity. However, leaf photosynthetic nitrogen demand may influence the leaf nitrogen response to soil nitrogen supply; thus, responses to nitrogen supply are expected to be the largest in environments where demand is the greatest. Using a nutrient addition experiment replicated across 26 sites spanning four continents, we demonstrated that climate variables were stronger predictors of leaf nitrogen content than soil nutrient supply. Leaf nitrogen increased more strongly with soil nitrogen supply in regions with the highest theoretical leaf nitrogen demand, increasing more in colder and drier environments than warmer and wetter environments. Thus, leaf nitrogen responses to nitrogen supply are primarily influenced by climatic gradients in photosynthetic nitrogen demand, an insight that could improve ESM predictions.

Study of metabolite profiles in winter wheat cultivars induced by Fusarium infection - K. Stuper-Szablewska; D. Kurasiak-Popowska; J. Nawracała; J. Perkowski (Cereal Research Communications, 2016)

Inhaled Pyrazinoic Acid Esters for the Treatment of Tuberculosis - E. F. Young; E. Perkowski; S. Malik; J. D. Hayden; P. G. Durham; L. Zhong; J. T. Welch; Miriam S. Braunstein; Anthony J. Hickey (Pharmaceutical Research, 2016)

SH waves in a layer with temperature dependent properties - Stanisław J. Matysiak; Radosław Mieszkowski; Dariusz M. Perkowski (Acta Geophysica, 2014)

Decomposition of non-ionic surfactant Tergitol TMN-10 by the Fenton process in the presence of iron oxide nanoparticles - L. Kos; K. Michalska; J. Perkowski (Environmental Science and Pollution Research, 2014)

Susceptibility of hulled and hulless barley doubled haploids to Fusarium culmorum head blight - T. Warzecha; T. Adamski; Z. Kaczmarek; M. Surma; P. Goliński; J. Perkowski; J. Chełkowski; H. Wiśniewska; K. Krystkowiak; A. Kuczyńska (Cereal Research Communications, 2010)

Reduction of Yield and Mycotoxins Accumulation in Oats Cultivars After Fusarium Culmorum Inoculation - J. Perkowski; I. Kiecana (Cereal Research Communications, 1997)

Natural Occurrence of Fusarium Mycotoxins in Polish Cereals - J. Perkowski; J. Stachowiak; I. Kiecana; P. Goliñski; J. Chelkowski (Cereal Research Communications, 1997)

Head infection and accumulation of Fusarium toxins in kernels of 12 barley genotypes inoculated with Fusarium graminearum isolates of two chemotypes - J. Perkowski; I. Kiecana; U. Schumacher; H.-M. Müller; J. Chełkowski; P. Goliński (European Journal of Plant Pathology, 1997)